Fairy-tale revivals in the long nineteenth century.
1 online resource.
Keywords: Volume two explores the way a wide range of classic princess tales written by marginalized writers. Rapunzel and Snow White, with their pale skin or long ropes of golden hair, are particularly popular vehicles for exploring and challenging racialized constructions of beauty. Marriage is the traditional vehicle of a happy ending in Princess tales, so marginalized responses to these tales also inherently respond to the doubly colonized position of women in the Anglophone world. The institution of marriage typically exposes the institutional oppression of colonized women. Authors include Charles Chesnutt, Jessie Fauset, Julia Kavanaugh, George Edwards, some of the unpublished manuscripts of Jewish-Australian author Joseph Jacobs, and the earliest work of Sinad de Valera, as well as fin-de-sicle illustrators such as Harry Clarke, and collected oral tales.